2019
DOI: 10.1021/acscatal.8b05164
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Mannich Reaction of α-Fluoronitriles with Ketimines: Enantioselective and Diastereodivergent Construction of Vicinal Tetrasubstituted Stereocenters

Abstract: Diastereodivergent and enantioselective conversion of isatin ketimines to α-fluoro-β-aminonitriles with vicinal tetrasubstituted stereocenters is achieved by a chiral copper complex/guanidine base catalyzed Mannich reaction with proper choice of the bisphosphine ligand. The reaction is broad in scope, scalable, and provides efficient access to a series of 3-aminoindolinones exhibiting a quaternary carbon-fluorine stereocenter with high yields and stereoselectivities. Selective transformations of the Mannich re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…The optimized method worked for both alkenyl-and alkynyl-substituted ketiminoesters and provided the corresponding products in 81-96% yields with 60-92% ee and 70-90% yields with 88-92% ee, respectively. while yields were comparable (89,92,91,89, and 91%, respectively). On the basis of the preliminary 1 H NMR study of β-ICD and phenolic additives, they proposed that a BINOL bridged a ketiminoester and a β-ICD-acrolein adduct through hydrogen bonding, leading to a more organized transition state.…”
Section: Acyclic Ketimines Bearing a Carbonyl Moietymentioning
confidence: 87%
See 1 more Smart Citation
“…The optimized method worked for both alkenyl-and alkynyl-substituted ketiminoesters and provided the corresponding products in 81-96% yields with 60-92% ee and 70-90% yields with 88-92% ee, respectively. while yields were comparable (89,92,91,89, and 91%, respectively). On the basis of the preliminary 1 H NMR study of β-ICD and phenolic additives, they proposed that a BINOL bridged a ketiminoester and a β-ICD-acrolein adduct through hydrogen bonding, leading to a more organized transition state.…”
Section: Acyclic Ketimines Bearing a Carbonyl Moietymentioning
confidence: 87%
“…Their preliminary mechanistic study indicated that the addition of a ketoacid to a ketimine preceded the decarboxylation process with their catalytic system. In 2019, Wolf and coworkers developed a copper-catalyzed stereodivergent asymmetric Mannich reaction of isatin-derived ketimines and α-fluoro-α-arylnitriles (Scheme 18) [89]. A chiral cuprous keteniminate complex generated from α-fluoro-αarylnitrile, a chiral copper catalyst, and BTMG was proposed as a nucleophile.…”
Section: Direct Mannichmentioning
confidence: 99%
“… [9] Although a similar strategy was later adopted by Wolf et al. using α‐fluoronitriles and activated imines derived from oxindoles to deliver highly congested substructures, [10] construction of the corresponding α‐fluoro‐β‐hydroxyl analogs using aldehydes instead of imines as electrophiles remained an unmet challenge. Such products are accessible via catalytic asymmetric aldol reactions of fluorinated carbonyl compounds, [11] but these prior works require indirect enolization, e.g., preformation of silyl enol ethers [12] and detrifluoroacetylation [13, 14] of engineered carbonyl substrates, resulting in protocols with poor atom economy [15] .…”
Section: Methodsmentioning
confidence: 99%
“…[8] In our continuing efforts to develop the reaction based on in situ-generated a-cyanocarbanions, we documented that a-fluoronitriles are complementary pronucleophiles for the addition of activated imines to provide acyclic scaffoldsw ith at etrasubstituted fluorine-containing stereogenic center (Scheme1c). [9] Although as imilar strategy was later adopted by Wolf et al using a-fluoronitriles and activated imines derived from oxindoles to deliver highly congested substructures, [10] construction of the corresponding a-fluoro-b-hydroxyl analogsu sing aldehydes instead of iminesa se lectrophiles remained an unmet challenge. Such products are accessible via catalytic asymmetric aldol reactions of fluorinated carbonyl compounds, [11] butt hese prior works require indirect enolization, e.g.,p reformation of silyl enol ethers [12] and detri-Scheme1.Compilation of catalytic asymmetric reactionsofinsitu-generated a-fluoro carbanions to construct tetrasubstituted fluorine-containings tereogenicc enters under proton-transfer conditions.…”
mentioning
confidence: 99%
“…[2m,6,7] Furthermore,t he stereodivergent synthesis of fluorinated compounds containing two or more vicinal stereogenic centers is much underdeveloped. [8] Meanwhile,t he pyridine ring is among the most prevalent heterocyclic structural moieties existing in biologically active natural products,p harmaceuticals,a nd agrochemicals. [9,10] Chiral molecules containing both ap yridine ring and af luorine atom attached to vicinal stereogenic centers might have great potential applications.…”
mentioning
confidence: 99%